2018
DOI: 10.1200/jco.2017.75.2931
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab Maintenance Versus No Maintenance During Chemotherapy-Free Intervals in Metastatic Colorectal Cancer: A Randomized Phase III Trial (PRODIGE 9)

Abstract: Purpose Conflicting results are reported for maintenance treatment with bevacizumab during chemotherapy-free intervals (CFI) in metastatic colorectal cancer after induction chemotherapy. Patients and Methods In this open-label, phase III, randomized controlled trial, we compared the tumor control duration (TCD) observed with bevacizumab maintenance and with no treatment (observation) during CFI subsequent to induction chemotherapy with 12 cycles of fluorouracil, leucovorin, and irinotecan plus bevacizumab. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 20 publications
1
72
0
2
Order By: Relevance
“…The prognosis of patients with CRC is poor (2,3); that is, more than half of patients will ultimately develop metastases (4)(5)(6). The median overall survival (OS) in patients with mCRC is ∼30 months (7) due to the availability of several chemotherapy drugs and targeted drugs as well as the development and popularization of multidisciplinary treatment models (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of patients with CRC is poor (2,3); that is, more than half of patients will ultimately develop metastases (4)(5)(6). The median overall survival (OS) in patients with mCRC is ∼30 months (7) due to the availability of several chemotherapy drugs and targeted drugs as well as the development and popularization of multidisciplinary treatment models (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Whether the effect on PFS can be ascribed to the use of bevacizumab, capecitabine or the combination is not known. The use of bevacizumab alone as maintenance in the French PRODIGE 9 study did not reveal any superiority [57].…”
Section: Should Bevacizumab In the Absence Of Clear Contraindicationsmentioning
confidence: 79%
“…28 Furthermore, the PRODIGE 9 Phase III trial of bevacizumab maintenance treatment found no benefit over observation alone, against a range of endpoints. 29 A meta-analysis of bevacizumab-based maintenance therapy reported improvements in time-tofailure-of-strategy and PFS, and a trend to improvements in OS, compared with complete stop. 30 As patients in this analysis of maintenance therapy are anti-EGFR-experienced and a selection bias may therefore exist, this should be borne in mind when considering the observed toxicity profilespatients who discontinued treatment due to unacceptable toxicity were not evaluated.…”
Section: Discussionmentioning
confidence: 99%